PENGARUH PENERAPAN FUNGSI MANAJEMEN TERHADAP DISIPLIN KERJA PEGAWAI NEGERI SIPIL PADA KANTOR PERTANAHAN KABUPATEN BONE BOLANGO - Zulkarnain Ilyas Idris (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
Discipline is the operative functions of the Human Resources management so interesting conversation in an organization, because the better disciplined employee, the higher the performance that can be achieved. The purpose of this study was to determine the effect of the application management function, organizing function, the function of directing and control functions partially or simultaneously to discipline employees working at the Land Office in Bone regency Bolango This research was conducted by using the design of the survey to obtain information on issues that deals with the study variables. Respondents were used as a sample in this study as many as 29 people or all members of the population sampled, so that the determination of the sample in this study is called saturated sample or census. The analytical tool used is multiple regression analysis. The results showed that partially independent variable in the form of a variable of planning, organizing, directing and monitoring has significant influence and valid on the dependent variable is the discipline of employees working at the District Land Office in Bone Bolango. Likewise, the simultaneous influence of independent variables with the dependent variable is significant.